Ultrafast X-ray measurements of the glass-like, high-frequency stiffness of aqueous solutions. Issue 31 (27th July 2017) - Jiao, Yishuo; Adams, Bernhard; Rose-Petruck, Christoph
Abstract : The ultrafast dynamics of the domains surrounding solutes in aqueous solution were measured using laser-generating GHz phonons in 30 mM ferrocyanide solutions and the resulting molecular motions of the solutes and their hydrogen-bonded solvation shells were detected using ultrafast X-ray absorption spectroscopy (UXAS). Abstract : The ultrafast dynamics of the domains surrounding solutes in aqueous solution were measured using laser-generating GHz phonons inside of 30 mM ferrocyanide solutions and the resulting molecular motions of the solutes and their hydrogen-bonded solvation shells were detected using ultrafast X-ray absorption spectroscopy (UXAS). The measurements of the phonon dynamics around the solutes showed that the domains had a glass-like stiffness on a timescale of tens of picoseconds.